Presentasi Bokong dan Kek : (Studi Kasus Terhadap Ny S di Puskesmas Lebaksiu Kabupaten Tegal) - Afidatul Awaliyah; Nora Rahmanindar; Meyliya Qudriani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
The Maternal Mortality Rate (MMR) in Tegal Regency in 2022 reached a high number, namely 27 cases, 13 of which occurred during the postpartum period, 10 cases during pregnancy, 4 cases during childbirth. Based on data obtained from the Lebaksiu Community Health Center from September to October 2023, there were no maternal and infant deaths. The number of pregnant women at high risk was 115 cases. These include pregnant women with breech presentation, Chronic Energy Deficiency (CED), age < 20 years, age > 35 years, child spacing < 2, history of CS, TB < 145 cm, HBSAg (+), HIV (+), anemia, history asthma, grand multipara, history of abortion, history of PEB and syphilis (+). The aim of this study was to examine obstetric cases with breech presentation and CED. This research uses a case study approach. The research subject was pregnant mother Mrs. S is 24 years old with breech presentation and CED. Data was taken from September to November 2023. Data was taken using interviews, observation and documentation, the results during the subject's pregnancy were successful in making the pregnancy normal. However, during labor, fetal hypoxia was experienced, so collaboration was carried out with the doctor, after management was carried out according to the doctor's advice, the fetal condition was normal and a SC delivery was carried out. During the postpartum period and the newborn is in normal and healthy condition. Suggestion: it is hoped that if a similar case is found there needs to be collaboration with doctors during pregnancy until postpartum, apart from that it is necessary to involve the family during pregnancy until postpartum.